(untitled) (Research, Society and Development, 2021)
To identify the incidence of human papillomavirus (HPV) with the presence of other microorganisms. This is a cross-sectional study composed of 128 women who were attended in the basic health units, between 2014 and 2018, to perform the Pap smear. The presence of papillomavirus was investigated using conventional PCR with primers MY09/11 and GP5 +/6+ (echo and endocervix cells) and the smear bacterioscopy of vaginal secretions was performed to identify the microorganisms. Statistical was performed using the square test, including a risk ratio or 95% confidence interval. HPV infection was identified in 48.4% (n = 62) women. Corynebacterium sp (39.8%) was the most prevalent microorganism, followed by Escherichia coli (21.1%), Staphylococcus aureus (14.0%), Gardnerella vaginalis (13.2%) and Candida albicans (7%), respectively. According to statistical analysis or HPV and the group of potentially pathogenic microorganisms had a significant association p <0.02. Corynebacterium sp showed an effective protection (0.356 [0.170-0.744] <0.05) in relation to sociodemographic, gynecological and obstetric factors. Only vaginal discharge and pH had p <0.05 when comparing the presence of infection. The other variables showed no statistical differences. This study revealed an association between the presence of pathogenic microorganisms with HPV virus infection, confirming a need for a better understanding of the female genitals’ microbiota. Thus, research involving the vaginal infectious agents, methods of protection and rapid diagnosis to contribute to the reduction of the number of lesions in the cervix and cervical cancer are needed.